Analysis of care given to patients with hypertension in Belo Horizonte, according to telephone survey - Tatiana Dias Paulucci; Gustavo Velasquez-Melendez; Regina Ivata Tomie Bernal; Francisco Félix Lana; Deborah Carvalho Malta (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: To examine the care given to patients with hypertension in the Brazilian public and private health services in the population of Belo Horizonte, Minas Gerais. METHODS: Telephone interviews were conducted in a sample of hypertensive adults in the year 2009, in Belo Horizonte (n = 100). We compared the care provided to hypertensive users of the Unified Health System (SUS) and of the Supplementary Health (SS), using the χ2 test or Fisher's exact test. The prevalence ratio was calculated by the Poisson regression model, adjusted for the variables age, education and skin color. RESULTS: In the descriptive analysis, hypertensive users of private health plans had a higher frequency of physician referral and greater blood pressure control. Unified Health System users were the ones who participated in health promotion groups the most. The acquisition of antihypertensive medications by beneficiaries of private health insurance was more frequent in private pharmacies, and in Health Centers among users of the Unified Health System. The differences disappeared when adjusting the variables for age, race and education. There was no difference regarding the guidance received for a change of habits, or regarding the incorporation of these healthy practices promotion by hypertensive patients. CONCLUSION: A healthier diet, the practice of physical activity, and the non-use of alcohol and tobacco have been incorporated by hypertensive patients, whether owning private health insurance or not. Promotion practices, proper use of medication a clinical follow-up are important for the control of blood pressure levels.